Potential Immunomodulating Activity Of Neem (Azadirachta Indica) Leaf Extracts And Its Bioactive Compound N-Acetylglucosamine In Mice - Kumar, Venugopalan Santhosh (2018)
Present study was aimed to evaluate the potential immunostimulant activity of NAcetylglucosamine (NAG) from Azadirachta indica leaves in mice. The hexane, chloroform, methanol and aqueous extracts of A. indica leaves were prepared and its immunostimulant activity was studied. The aqueous extract of A. indica leaves (AEAIL) showed significant (P< 0.001) higher immunostimulant activity than other extracts. Hence, isolation of possible phytoconstituent(s) from AEAIL was carried out and the N-Acetylglucosamine (NAG) was isolated. The NAG was administered at 266, 400 and 800 μg/kg of mice, intraperitoneal route weekly for 4 weeks to evaluate immunostimulant activity.